1975
DOI: 10.1021/jf60199a025
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and environmental fate of 1-(2,6-difluorobenzoyl)-3-(4-chlorophenyl)urea

Abstract: Radiolabeled preparations of the insect growth regulator PH-6040 were evaluated for degradation in a laboratory model ecosystem and after exposure to sheep microsomes, Pseudomonas, soil, and ultraviolet light. The parent compound was found to be moderately stable but was not highly concentrated through food chains or by direct ab-sorption from water. The degradative pathways were almost entirely through cleavage between the carbonyl and amide groups of the urea bridge to give 2,6-difluorobenzamide and 2,6-difl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 11 publications
1
47
1
1
Order By: Relevance
“…Hydrolysis has been identified as probably the major route of benzoylphenyl urea detoxification in studies done with diflubenzuron [61][62][63][64]. The major hydrolytic metabolites of diflubenzuron in S. littoralis larvae are 4-chloroaniline and 4-chlorophenylurea [7].…”
Section: Detoxifying Enzymes and Their Importance In Resistance Mechamentioning
confidence: 99%
“…Hydrolysis has been identified as probably the major route of benzoylphenyl urea detoxification in studies done with diflubenzuron [61][62][63][64]. The major hydrolytic metabolites of diflubenzuron in S. littoralis larvae are 4-chloroaniline and 4-chlorophenylurea [7].…”
Section: Detoxifying Enzymes and Their Importance In Resistance Mechamentioning
confidence: 99%
“…Studies on the environmental degradation of TH-6040 by Metcalf et al (27) showed that it is moderately persistent in their laboratory model ecosystem in alga, snail, caterpillar, and mosquito larva. The fish, Gambusia spp., was able to metabolize it very efficiently which demonstrated no bioconcentration.…”
mentioning
confidence: 99%
“…Diflubenzuron was not metabolized by the salt marsh caterpillar, Estigmene acrea, (Metcalf et al, 1975), the boll weevil, Anthonomous grandis, (Still and Leopold, 1975) or Pieris brassicae larvae (Verloop and Ferrell, 1977). Diflubenzuron was degraded only to a very limited extent by sheep liver microsomes (Metcalf et al, 1975) but was extensively metabolized after oral administra tion to laboratory rats (Verloop and Ferrell, 1977). Ivie (1978) reported that the major metabolites of diflubenzuron excreted by the cow and sheep resulted from hydroxylation on the difluorobenzoyl and chlorophenyl rings and by the cleavage between the carbonyl and amide groups to give metabolites that were excreted either free or as conjugates.…”
Section: Abidmentioning
confidence: 93%
“…A thorough evaluation of the environ mental fate of diflubenzuron is, therefore, of utmost impor tance. Studies by Metcalf et al (1975) showed that difluben zuron was moderately stable in a model ecosystem, but the compound was not highly concentrated through food chains or by absorption from water. Diflubenzuron was not metabolized by the salt marsh caterpillar, Estigmene acrea, (Metcalf et al, 1975), the boll weevil, Anthonomous grandis, (Still and Leopold, 1975) or Pieris brassicae larvae (Verloop and Ferrell, 1977).…”
Section: Abidmentioning
confidence: 99%
See 1 more Smart Citation